Breaking from Traditionalism: Strategies for the Recruitment of Physical Education Teachers. Issue 2 (12th February 2018) - O'Neil, Kason; Richards, K. Andrew R.
Abstract : Teacher education programs across the country are being asked to systematically and deliberately recruit teacher candidates who are not only highly qualified, but represent diverse backgrounds. Coupled with dwindling enrollments, these programs may want to reevaluate the types of students recruited into a career in physical education. This article uses occupational socialization theory as the framework for discussing how breaking away from traditional recruitment strategies may be necessary to keep physical education teacher education programs thriving. To address this point, current recruitment practices in physical education teacher education are critiqued, and nontraditional strategies for recruiting highly qualified candidates who also represent diverse backgrounds are discussed. It is argued that the future of the physical education discipline rests on the ability to recruit and train students who are focused on lifetime physical activity rather than team sports.